Análise da relevância clínica da classificação histológica dos carcinomas de mama de tipos lobular e ductal e sua relação com a classificação molecular - Moraes Neto, Francisco Alves [UNESP] (2014)
INTRODUCTION: The prognostic value of the molecular classification of breast cancer recently proposed has been validated by many studies. However, the great majority of these studies has focused on invasive ductal carcinoma no special type (IDC), a widely recognized heterogeneous entity. Few papers have studied other special types of breast cancer such as invasive lobular carcinoma (ILC) the most common special type. ILC shows clinico-pathological features and natural history quite distinctive from IDC being clearly separate biologic entities. Moreover, ILC is relatively frequent and has been increasing in incidence over the recent years. OBJECTIVE: to study comparatively the luminal molecular subtypes A e B of two groups of patients with ILC and IDC and to determine the prognostic independent value of the molecular classification in ILC patients by correlating the molecular subtypes with clinical outcomes such as breast cancer specific survival (BCSS) and overall survival (OS). MATERIALS AND METHODS: archival paraffin blocks from women diagnosed with ILC and IDC at the Pathology Laboratory of Hospital Amaral Carvalho, Jau, Sao Paulo, Brazil, were retrieved. Patient's charts and the Hospital Amaral Carvalho Cancer Registry were consulted for obtaining the staging and follow-up information (median 121.77 and 131.27 months for ILC and IDC, respectively) and 186 patients were selected. Two samples from each paraffin block were extracted to mount tissue microarray (TMA) blocks by using a Tissue Microarray Builder ab1802 (Abcam®, Cambridge, UK). The following immunohistochemical markers were performed in the TMA blocks: estrogen receptor α, progesterone receptor, HER2 and Ki67 protein. The intrinsic molecular subtypes (luminal A, luminal B, HER2 and triple negative) were determined based on the immunohistochemical profile of each tumor. Prognostic clinico-pathological features were analysed in absolute (n) and relative frequency (%). The ...